Forest products industry risk based lending guidelines - Fry, Cary G. (Kansas State University, 2016)
Institutions within the Farm Credit System (FCS) make risk-based lending decisions. As a primary lender to agriculture, these decisions are based on qualitative and quantitative procedures based on guidelines created for the purpose of measuring financial risk or the future probability that a loan will be in default of full repayment. As the risk increases, the cost to the FCS institution also increases to support a higher risk, higher probability of delinquency. Concentration risk, intrinsic risk, transaction risk, repayment risk, reputation risk are just a few examples of risk-based lending decisions. Under regulatory direction, FCS institutions have a charter to provide financing to agriculture’s food and fiber industries. The forest products industry is a large commodity borrower of risk-based financing within the FCS, specifically in the Pacific Northwest. Among other commodities, Northwest Farm Credit Services (Northwest FCS) supports the forest products industry through financial lending products. A majority of agricultural commodities reflect cycles of robust earnings and weak profits based on macro- and micro-economic indicators. The United States forest products industry had a period of strong earnings based primarily on the housing bubble between 2002-2007. With the U.S. economic recession beginning in 2008, the forest products industry also waned from 2008-2012. This impact resulted in financial stress for many forest product companies, both nationally and internationally. Due to the downturn in the forest products industry, regulators were quick to position the industry with high risk-based assumptions, thus putting pressure to Northwest FCS’ risk-guidelines in supporting that historical analysis accurately depicted industry risk. The purpose of this thesis is threefold: to study the correlation between different major commodity groups to better understand the value of a commodity concentration limit as a way to mitigate portfolio risk for Northwest FCS; to support analysis used by Northwest FCS and their ability to calculate the likelihood of financial stress; and provide customer-based feedback by way of a survey from forest products companies in the industry, as additional support to assumptions that were used to calculate certain subjective criteria for estimating risk. As one method to analyze financial risk, customer data was collected for the years ending 12/31/2008, 12/31/2011, and 12/31/2014. Statistical regression analysis was used to measure financial stress migration based on companies in the forest products industry. The regression analysis indicates financial measures of liquidity, leverage, and cash flow used for such calculated stress, specifically prior to the economic downturn of 2008, through the downturn of 2008-2012, and post-recovery of the forest products industry are correlated with measuring financial risk. As a risk mitigation tool, the board of directors that governs Northwest FCS hold a commodity concentration limit of fifteen percent (15%) for the forest products industry. The customer survey provided information that allowed Northwest FCS to create subjective rating criteria for calculating risk. A guideline was created to assess subjective criteria provided by forest products customers on the same level based on the feedback provided which may be beneficial for understanding current results and potential future subjective risk associated within the industry.
Keywords: Forest products; Risk; Lending; Finance; Agriculture; Default (loan)